مقياس مقترح للدراسات المسحية وتأثير معامل الخبرة في مشاريع التشييد - مصطفى ماهر (Latakia University Journal -Engineering Sciences Series, 2018)
Likert questionnaires are widely used in survey research, it is applied as one of the most fundamental and frequently used tools in construction management sciences research, especially when there isn’t historical data. Simultaneously, it is also subjected to a lot of debatesand controversies in regards with the analysis and inclusion of points on the scale. With thiscontext, through reviewing the available literature, which used Likert questionnaires, there are a part concerning of the experts of sample’s individuals, these data don’t use inanalytical study. Also, the construction data are quantities then change into qualities phrases the change into quantities data by ordinal Likert scale. This paper attempts to gradually build a ratio scale from 0-100%, and take into account the effect ofthe experts of sample’s individuals by linear scale.The purpose of this paper is to describe the process for developing reliable and valid measurementinstruments that can be used in any construction industry field research setting. لقد تم استخدام الاسلوب المسحي في أغلب الدراسات في مجال ادارة التشييد خصوصا عند عدم وجود بيانات موثقة من المشاريع السابقة. إن البيانات المسحية التي يتم الحصول عليها في مجال التشييد هي بالأصل كمية و يتم التعبير عنها بالاستبيان بشكل لفظي و من ثم يتم التعبير عنها بشكل كمي بالاعتماد على مقياس ليكرت الرتبي (الثلاثي أو الرباعي أو الخماسي) و قد تعرض هذا الاسلوب في القياس لانتقادات و خلافات كثيرة ولاسيما دراسات و أبحاث العلوم التربوية و الانسانية. أما في مجال صناعة التشييد فقد تم استخدام الاستبيان في دراسات كثيرة جدا للحصول على بيانات البحث. حيث يتم تقسيم الاستبيان لأجزاء: يتناول الجزء الاول البيانات العامة و لا يتم استخدامها بالشكل المناسب و تبقى بيانات للعرض و لا يتم تحليلها و الافادة منها، فبيانات الخبرة و عدد المشاريع التي عمل بها لا تؤثر على النتائج و يتم التعامل مع جميع افراد العينة بشكل متساوي و لا تؤخذ سنوات الخبرة و عدد المشاريع بالاعتبار. تم في هذا البحث اقتراح مقياس نسبي من 1-100% و يمكن استخدام هذا المقياس بسهولة و يعكس الواقع الحقيقي للبيانات الحقلية و تم ايضا اقتراح طريقة لمعالجة البيانات المتعلقة بالخبرة بالاعتماد على الاسلوب الخطي، و يأخذ تأثيرها بالاعتبار على النتائج.